ทัศนคติต่อการอนุรักษ์งานใบตอง ดอกไม้ เครื่องสด ของนักศึกษาคณะเทคโนโลยีคหกรรมศาสตร์ มหาวิทยาลัยเทคโนโลยีราชมงคล - ไวเชียงค้า อัครพล (RMUTP Research Journal Sciences and Technology, 2015)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาและหาความสัมพันธ์ระหว่างทัศนคติต่อการอนุรักษ์งานใบตอง ดอกไม้ เครื่องสด ของนักศึกษาคณะเทคโนโลยีคหกรรมศาสตร์ มหาวิทยาลัยเทคโนโลยีราชมงคล กับปัจจัยส่วนบุคคล ปัจจัยภายใน และปัจจัยภายนอก กลุ่มตัวอย่างคือนักศึกษาระดับปริญญาตรีของคณะเทคโนโลยีคหกรรมศาสตร์ มหาวิทยาลัยเทคโนโลยีราชมงคล จำนวน 270 คน ได้จากการสุ่มแบบชั้นภูมิ เครื่องมือที่ใช้เป็นแบบสอบถามและแบบทดสอบ วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา และสถิติเชิงอนุมาน ผลการศึกษา พบว่า ทัศนคติต่อการอนุรักษ์งานใบตอง ดอกไม้ เครื่องสด อยู่ในระดับปานกลาง ภูมิลำเนา การศึกษาของผู้ปกครอง อาชีพของผู้ปกครอง ความรู้ด้านงานใบตอง ดอกไม้ เครื่องสด ความภาคภูมิใจในงานใบตอง ดอกไม้ เครื่องสด การจัดการเรียนการสอน และการจัดหลักสูตรการเรียนการสอน มีความสัมพันธ์กับทัศนคติ ต่อการอนุรักษ์งานใบตอง ดอกไม้ เครื่องสด อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ส่วน เพศ และระดับชั้นปีที่ศึกษา ไม่มีความสัมพันธ์กับทัศนคติ ต่อการอนุรักษ์งานใบตอง ดอกไม้ เครื่องสด Abstract The purposes of this research were to study and explore the relationship between the attitudes toward the preservation of banana-leaf crafts, flower works and decoration of fresh flowers of the Faculty of Home Economics Technology students, Rajamangala University of Technology and individuals, as well as internal and external factors. Research samples were 270 undergraduate students of the Faculty of Home Economics Technology from Rajamangala University of Technology Phra Nakhon, Rajamangala University of Technology Krung Thep, and Rajamangala University of Technology Thanyaburi. The samples were selected by using stratified sampling. The research methods were questionnaires and testing forms. Data analysis was performed by descriptive statistics and inferential statistics. The results of the study revealed that the attitudes toward the preservation of banana-leaf crafts, flower works and decoration of fresh flowers of the Faculty of Home Economics Technology students, Rajamangala University of Technology were at the medium level. Backgrounds, parents’ education, parents’ occupations, knowledge on banana-leaf crafts, flower works and decoration of fresh flowers, pride on banana-leaf crafts, flower works and decoration of fresh flowers, learning management and curriculum management were related to the attitudes toward the preservation of banana-leaf crafts, flower works and decoration of fresh flowers at the statistical significance 0.05. As for gender and the year of study, they were not related to the attitudes toward the preservation of banana-leaf crafts, flower works and decoration of fresh flowers.